UJI HEMATOLOGI PASIEN TERDUGA DEMAM BERDARAH DENGUE INDIKASI RAWAT INAP - Juranah .; Darwati Muhadi; Mansyur Arif; Burhanuddin Bahar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Indonesia is an endemic area of Dengue Hemorrhagic Fever (DHF). The clinical symptoms of this disease varies; it can beasymptomatic or atypical fever. Therefore, the early detection of Dengue virus is important to reduce the incidence of new victims fromhis infection. The aim of this study was to find out the haematological features of DHF suspected patients indicated for hospitalization. Aross-sectional study was done on DHF suspected patients indicated for hospitalization. The data were obtained from the Medical Recordat Wahidin Sudirohusodo Hospital from January-July 2009. The data were presented in the form of table. The results showed that themean leukocyte counts was 5.138 103/µL ranging from 2.10–16.70 103/µL, the mean erythrocyte count was 5.136 106/µL rangingrom 3.2–6.40 106/µL, the mean platelet count was 111.27 103/µL ranging from 11.40–260 103/µL. The DHF patients at admissionwho had leucositopenia, thrombocytopenia, and monocytosis were 54.30%, 71.40%, and 51.40%, respectively. Based on the result itan be concluded, that the most common haematological abnormality in DHF suspected patients whom indicated for hospitalizationwere thrombo cytopenia, leucocytopenia and monocytosis.